2022
DOI: 10.1039/d2fo00983h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decaffeinated green coffee extract supplementation on anthropometric indices, blood glucose, leptin, adiponectin and neuropeptide Y (NPY) in breast cancer survivors: a randomized clinical trial

Abstract: Objective: The aim of this study was to evaluate the effects of decaffeinated green coffee extract (DGCE) supplementation on anthropometric indices, blood glucose, leptin, adiponectin and Neuropeptide Y (NPY) in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…A recent meta-analysis of eight trials found that GCE supplementation (dosage 50–1,200 mg/d, duration of 8–12 weeks) has no effect on CRP ( 19 ). However, based on the results of this meta-analysis, GCE supplementation has a decreasing effect on tumor necrosis factor alpha (TNF-α) as an inflammatory biomarker ( 37 ). CGA, by increasing the expression of genes encoding enzymes, including glutathione peroxidase and superoxide dismutase, exerts reducing effects on oxidative stress ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of eight trials found that GCE supplementation (dosage 50–1,200 mg/d, duration of 8–12 weeks) has no effect on CRP ( 19 ). However, based on the results of this meta-analysis, GCE supplementation has a decreasing effect on tumor necrosis factor alpha (TNF-α) as an inflammatory biomarker ( 37 ). CGA, by increasing the expression of genes encoding enzymes, including glutathione peroxidase and superoxide dismutase, exerts reducing effects on oxidative stress ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Y1R expression was upregulated by 17β-estradiol and downregulated by the anti-estrogen agent fulvestrant in breast cancer cells (MCF-7), whereas tamoxifen induced the total loss of Y1R in MCF-7 xenografts [ 104 ]. Supplementation with decaffeinated green coffee extract in breast cancer survivors with obesity did not affect serum NPY levels [ 105 ]. However, social isolation increased the risk of cancer development and NPY levels [ 106 ], and in an experimental model of breast cancer, chronic stress increased the extent/frequency of bone metastases [ 107 ].…”
Section: Involvement Of Neuropeptide Y Peptide Yy and Pancreatic Poly...mentioning
confidence: 99%